(untitled) (PERcursos Linguísticos, 2020)
This research investigated the vision, beliefs and academic literacy practices of UFMG undergraduates who attended the Portuguese Language Workshop: Reading and Text Production, in the first semester of 2018, in order to clarify the demands of these students. students and their relationship with knowledge in the context of higher education. The study was based on the theories of academic literacy (LEDA; STREET, 1988, 2014) and the research data, of a qualitative and quantitative nature, were collected through a questionnaire, answered in the Moodle environment. The results revealed that many respondents recognize the importance of basing their search on books and scientifically credible portals, as well as worrying about plagiarism. However, there are aspects, such as the preference for common research sites and the little knowledge of academic genres, that require us, as trainers of these students, a reflection and a change in pedagogical strategy.